2005
DOI: 10.1007/s00701-004-0405-2
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of aorta and inferior vena cava during lumbar disc surgery

Abstract: Major vascular injury during lumbar disc surgery has been recognized as an unusual but well described complication. A potentially fatal outcome can be avoided by a high index of suspicion and an early diagnosis. We present a rare case of aortic and inferior vena caval injury in a 50-year-old female patient undergoing intervertebral disc surgery at lumbar one and two levels. A quick diagnosis and prompt management resulted in a favourable outcome for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 7 publications
0
48
0
1
Order By: Relevance
“…We believe that the aggressive manipulations of the spinal surgeon and the sharpness of the scalpel led to the anterior movement of the fragment. In 1953, Leavens and Bradford reported that the defects in the anterior annulus fibrosus and longitudinal ligaments could allow great vessel injuries during spinal surgery (3,5), which could have contributed to the complication in this case.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We believe that the aggressive manipulations of the spinal surgeon and the sharpness of the scalpel led to the anterior movement of the fragment. In 1953, Leavens and Bradford reported that the defects in the anterior annulus fibrosus and longitudinal ligaments could allow great vessel injuries during spinal surgery (3,5), which could have contributed to the complication in this case.…”
Section: Discussionmentioning
confidence: 84%
“…Lacerations to vessels are early vascular complications while arteriovenous fistulas and pseudoaneurysms are defined as late vascular complications (5). The present early complication developed after part of a broken scalpel blade was lost during posterior microdiscectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients undergoing lumbar disc surgery, major vascular injuries are rare but very serious, life-threatening complications (1)(2)(3)(4)(5). During the operation, in case of sudden hemodynamic instability, considering the possibility of a major vascular injury and dynamic intervention can be lifesaving (1)(2)(3)(4)(5) De Saussure has reported 106 cases of vascular injury due to lumbar disc surgery in 1958(4).…”
Section: Discussionmentioning
confidence: 99%
“…Major vascular injury is one of them and it may be fatal if not noticed in time (1). This type of injury is more common especially during lumbar region intervertebral disc surgery, due to proximity of the anterior longitudinal ligament and major vascular structures located anteriorly (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%